The Solubility Limit of CaO in α‐Alumina at 1600°C. Issue 10 (10th June 2013) - Akiva, Ran; Berner, Alex; Kaplan, Wayne D.; Rohrer, G. S.
<x xml:space="preserve">Abstract</x> The solubility limit of Ca in 99.99% pure α‐Al2O3 (alumina) was measured using a wavelength dispersive spectrometer mounted on a scanning electron microscope. Al2O3 samples were equilibrated at a concentration which ensured saturation of the Al2O3 grains with Ca, and were quenched in water from 1600°C. The results were compared with those from samples which were furnace cooled from 1600°C. For the quenched samples, the Ca solubility limit was found to be 51 ± 1 ppm, which is significantly larger than the solubility limit for samples which were furnace cooled (26 ± 1 ppm).